Relative efficiency analysis of public hospitals in Costa Rica - Morera-Salas, Melvin (2015)
Data envelopment analysis helps determining which of hospitals have better relative performance and which could improve the use of resources. The objective is to analyze the hospitals technical efficiency in Costa Rica. Data for 2012-2013 of 23 general public hospitals come from CajaCostarricense de SeguroSocial.  We use data envelopment analysis to determine the efficiency of Costa Rican Public Hospitals. We use two inputs:spending hospitalization and hospital bed and three outputs:case mix adjusted hospital discharges, Functional Indexand adjusted in hospital mortality index.The efficiency level varies substantially among the 23 hospitals analyzed. In 2013, 30% of hospitals were technically efficient, this situation improved compared to 2012.This work is a first approach the analysis of efficiency of public hospitals in Costa Rica. An effort was made to standardize the data, adjusting the variables to consider the case mix and risk of cases in each hospital, so that results are comparable between centers of varying size and complexity. In conclusion, DEA results show that 70% of hospitals can improve the use of resources.